Antimicrobial activity of indigenous Oscillatoria spp. against prevalent bacterial diseases in fish and shellfish - Jannatul Nayeem; Sumit Kanti Dey; Proma Dey; Mohammed Abdullah Ayoun; Dipa Debi; Mohammed Nurul Absar Khan; Helena Khatoon (Aquaculture Reports)
Cyanobacteria have garnered attention as a prospective source of natural and sustainable antibiotics due to their diverse secondary bioactive compounds. Phenolic extracts of indigenous freshwater and marine Oscillatoria sp. were utilized to assess their antibacterial activity through the disk diffusion technique. Three gram-positive bacteria such as Staphylococcus sp.1,2 and Streptococcus sp. and nine gram-negative bacteria including Vibrio sp.1,2,3, Escherichia coli, Salmonella sp., Shigella sp., Aeromonas sp., Pseudomonas sp.1,2 was isolated from diseased marine fish and shellfish for the antibacterial activity assessment. Filamentous Oscillatoria sp. indicated higher antibiotic activity than planktonic one. Gram-positive bacteria showed higher susceptibility to phenol compared to gram-negative bacteria. Filamentous Oscillatoria sp. showed the highest inhibition zone of 34.06 ± 0.08 mm against Staphylococcus sp., while planktonic Oscillatoria sp. showed a lower inhibition zone of 17.11 ± 0.18 mm against Pseudomonas sp. A highest activity index (AI) value of 2.10 ± 0.03 was observed for filamentous Oscillatoria sp. against Staphylococcus sp., whereas a significantly lower AI value of 1.00 ± 0.01 was obtained for planktonic Oscillatoria sp. against Pseudomonas sp. Thus, Oscillatoria spp. contain potential antibacterial substances that facilitate detailed analysis of Oscillatoria spp. bioactive compounds for creating novel antibiotics and benefitting both aquaculture and pharmaceutical industries.